Telephonic Consultation: Modern Era of some Unsolved Questions - Patel, Umesh; Gedam, D Sharad; Prasad Patel, Narmada; Kumar Ratre, Bhupendra (International Journal of Medical Research and Review, 2014)
Improving access to healthcare is a major challenge for patients, doctors and community. Globally many traditional services which used to be delivered face to face (e.g. banking and shopping) are delivered now telephonically and electronically. Currently, telephonic consultation appears to be used for many different purposes despite scanty information and evidence on quality of method, pitfalls and limitations. However, despite the widespread use of telephones in daily life and the range of possible benefits that telephones may offer in medical services, their role in clinical practice remains highly controversial. Medical community find it difficult and less rewarding because of many factors and limitations. There is a need for focused research, proper training of medical professionals, specific guidelines on medico legal aspect and issue of professional fee need to be addressed for better utilization of seemingly useful and cost effective method of telephonic consultation in clinical practice.